Assessment of adherence to the core elements of hospital antibiotic stewardship programs: a survey of the tertiary care hospitals in Punjab, Pakistan - Mubarak, Naeem; Sarwar Khan, Asma; Zahid, Taheer; Ijaz, Umm e Barirah; Aziz, Muhammad Majid; Khan, Rabeel; Mahmood, Khalid; Saif-ur-Rehman, Nasira; Mohd Zin, Che Suraya (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Abstract: Background: To restrain antibiotic resistance, the Centers for Disease Control and Prevention (CDC), United States of America, urges all hospital settings to implement the Core Elements of Hospital Antibiotic Stewardship Programs (CEHASP). However, the concept of hospital-based antibiotic stewardship programs is relatively new in Low- and Middle-Income Countries. Aim: To appraise the adherence of the tertiary care hospitals to seven CEHASPs. Design and Setting: A crosssectional study in the tertiary care hospitals in Punjab, Pakistan. Method: CEHASP assessment tool, (a checklist) was used to collect data from the eligible hospitals based on purposive sampling. The check list had 19 statements to cover seven CEHASPs: Hospital Leadership Commitment, Accountability, Pharmacy Expertise, Action (Implement Interventions to Improve Antibiotic Use), Tracking Antibiotic Use and Outcomes, Reporting Antibiotic Use and Outcomes, and Education. For each statement, a response of “YES”, “NO” or “Under Process” constituted a score of 2, 0 and 1, respectively, where the higher the scores the better the adherence. Categorical variables were described through descriptive statistics, while independent t-test computed group differences. Result: A total of 68 hospitals (n = 33 public, n = 35 private) participated with a response rate of 79.1%. No hospital demonstrated “Perfect” adherence. Roughly half private (48.6%) and more than half public (54.5%) sector hospitals were “Poor“ in adherence. Based on the mean score, there was no significant difference between the private and the public hospitals in terms of comparison of individual core elements. The two most neglected core elements emerged as top priority area were: Reporting Antibiotic Use and Outcomes and Tracking Antibiotic Use and Outcomes. Conclusion: The current response of Pakistan to implement hospital-based antibiotic stewardship programs is inadequate. This study points out significant gaps of practice both in public and private tertiary care hospitals. A majority of the core elements of antibiotic stewardship are either absent or ”Under Process”. The deficiency/priority areas mentioned require immediate attention of the concerned stakeholders in Pakistan.